THE ROLE OF PSYCHOLOGICAL SERVICE IN HUMAN LIFE: AN ESSENTIAL COMPONENT FOR OPTIMAL WELL-BEING - Dilfuza Madgafurova (Galaxy International Interdisciplinary Research Journal, 2023)
Psychological services play a crucial role in enhancing human well-being and promoting optimal mental health. This scientific article explores the significant contributions of psychological services in various domains of human life. It discusses the importance of early intervention, prevention, and treatment of mental health disorders, as well as the provision of support for individuals facing significant life challenges. Additionally, it highlights the role of psychological services in fostering resilience, improving interpersonal relationships, enhancing performance in various settings, and promoting overall quality of life. By understanding the comprehensive role of psychological services, individuals, society, and policymakers can recognize the importance of investing in mental health resources.